Registration and evaluation of the hacienda system in the Chancay valley - Guzmán Juárez, Miguel (2024)
We present the current state of the hacienda system of the lower valley of Chancay, considering its temporality, since 1539. An emblematic territory for its different cultural traditions, evidencing the presence of unique settlements and buildings corresponding to the model, whose problems reflect neglect, deterioration and latent extinction; aiming to define what would be the heritage architectural values that they still preserve. The objective was to register and evaluate the haciendas to have an overview of the historical potential, identifying typologies, spatial organizations and contextual relationships, within social dynamics. Ethnohistorical documentation, sociological and anthropological investigations have been contrasted with architectural field work: survey of some hacienda houses, recording 15. They show different states of configurations and transformations—highlighting houses, chapels, factories and “rancherias”—; maintaining that perception of architecture articulated to the territory, consolidating landscapes. Architectural, typological-constructive, historical-symbolic and social identity values are revealed, with tourism potential, implementing management mechanisms and conservation of social memories.